CHICANAS AND LATINAS IN THE U.S. - Ochoa, Gilda (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course focuses on the experiences of Chicanas and Latinas in the United States. While Chicanas and Latinas often share experiences and outlooks with men of color and European American women, their experiences are left out of a framework that just looks at race, or just examines gender. This class marks a step in filling that space. In the first part of the course, we begin with analytical frameworks that center the perspectives of Chicanas and Latinas. Thereafter, we focus on how the institutions of migration, family, health, work, and education have blatantly, or sometimes, inadvertently perpetuated race and gender inequality. We also consider the ways that these institutions are related. Throughout the course we will highlight examples of resistance and strategies for building alliances. This course primarily focuses on Mexican Americans and Mexican immigrants, the largest group of Latinas/os in the United States. However, our readings and discussions will allow us to make comparisons by nationality, generation, and gender across and within Latinas/os in the U.S., including Central Americans and Caribbeans.